Coronary artery aneurysm presenting as a large mass encroaching on the right atrium in an adult patient with untreated Kawasaki disease. (27th March 2015) - Wassef, Nancy
Abstract : A 26-year-old man presented with atypical chest pain and dyspnoea for several days before admission that was not related to exertion. The patient had no medical history other than a long duration of fever and rash as a child, which resolved after a few weeks. The initial blood investigations showed thrombocytopenia and raised inflammatory markers with a negative troponin level. The patient had positive antiplatelet antibodies and was diagnosed with immune thrombocytopenic purpura (ITP). Echocardiography showed a large cystic mass at the right atrium. Coronary multislice CT showed a huge aneurysm at the origin of the right coronary artery (RCA), which was confirmed by coronary angiography. The patient received intravenous immunoglobulin and platelet transfusion before coronary artery bypass surgery and he had a successful resection of the aneurysm with a saphenous vein graft to distal RCA. The patient had a good recovery and was discharged home.